Deletion of a Gene Encoding a Putative Peptidoglycan-Associated Lipoprotein Prevents Degradation of the Crystalline Region of Cellulose in Cytophaga hutchinsonii - Wang, Xifeng; Wang, Zhiquan; Bai, Xinfeng; Zhao, Yue; Zhang, Weican; Lu, Xuemei (Frontiers in Microbiology, 2018)
Cytophaga hutchinsonii is a gliding Gram-negative bacterium in the phylum Bacteroidetes with the capability to digest crystalline cellulose rapidly, but the mechanism is unclear. In this study, deletion of chu_0125, encoding a homolog of the peptidoglycan-associated lipoprotein (Pal), was determined to prevent degradation of the crystalline region of cellulose. We found that the chu_0125 deletion mutant grew normally in regenerated amorphous cellulose medium but displayed defective growth in crystalline cellulose medium and increased the degree of crystallinity of Avicel. The endoglucanase and β-glucosidase activities on the cell surface were reduced by 60% and 30% without chu_0125, respectively. Moreover, compared with the wild type, the chu_0125 deletion mutant was found to be more sensitive to some harmful compounds and to release 6-fold more outer membrane vesicles (OMVs) whose protein varieties were dramatically increased. These results indicated that CHU_0125 played a critical role in maintaining the integrity of the outer membrane. Further study showed that the amounts of some outer membrane proteins were remarkably decreased in the chu_0125 deletion mutant. Western blotting revealed that CHU_3220, the only reported outer membrane protein that was essential and specialized for degradation of the crystalline region of cellulose, was largely leaked from the outer membrane and packaged into OMVs. We concluded that the deletion of chu_0125 affected the integrity of outer membrane and thus influenced the localization of some outer membrane proteins including CHU_3220. This might be the reason why deletion of chu_0125 prevented degradation of the crystalline region of cellulose.